Association between Body Mass Index and Type of Infection on the Severity of Dengue Infection in Bengkulu City, Indonesia - Annelin Kurniati; Dessy Triana; Enny Nugraheni Sulistiyorini; Mardhatillah Sariyanti; Gayatri Ghea Wirastari (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Background: Dengue virus infection is a serious global health problem. The incidence has increased rapidly within the last 50 years. The clinical manifestations vary from Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF), to Dengue Shock Syndrome (SSD). Some of the influencing factors are the Body Mass Index (BMI) and the type of dengue infection. The study aimed to determine the association between BMI and type of infection on the severity of dengue infection in adulthood.Methods: The study used a cross-sectional design with a total sample of 39 patients diagnosed with dengue infection and fulfilling the inclusion criteria. The sampling technique was consecutive sampling. The data analysis used was the Spearman correlation test. Data collection was conducted by distributing research form which cover sample characteristics, BMI values, clinical manifestations, types of infection and the severity of dengue infection.Results: The total of subject obtained was 37 respondents (23 male and 14 female). The average BMI value was 24.65 ± 5.08. The most common clinical manifestations were fever (100%), nausea/vomiting (91.8%), headache (89.1%), myalgia (89.1%), and arthralgia (72.9%). Most cases of dengue infection were in the normal BMI group and the highest degree of severity was DD. There was a significant relationship with a fairly strong correlation value between BMI and dengue severity (p=0.003; r=0.478). However, there was no significant relationship between the type of infection (p=0.987; r=0.03) with the level of dengue severity.Conclusion: Knowing the risk factors as predictors of dengue severity is very necessary in order to handle dengue infection quickly and accurately.